Pioneering Process Research: Andrew Pettigrew's Contribution to Management Scholarship, 1962–2014. (29th March 2015) - Sminia, Harry
Abstract : This paper assesses Andrew Pettigrew's contribution to management scholarship. This review addresses the process, content, and context of his research career. Chronologically, the process will be subdivided into three distinct phases: the period leading up to the establishment of the Centre for Corporate Strategy and Change, Pettigrew's time with the Centre, and Pettigrew's research since leaving the Centre. The content of Pettigrew's research focussed on big problems and emerging phenomena such as decision‐making, organisational culture, organisation development, strategic change, human resource management, competitiveness, new public management, boards of directors, innovative forms of organising, high‐performing research teams, and business schools. His contextualist methodology for process research will be explicated. Pettigrew's contribution will be contextualised by comparing it with contemporary research. The paper concludes that there is still a need not only to examine big problems and emerging phenomena but also to provide a processual understanding of management reality. There is a need to further develop process research methodologies such as Pettigrew's contextualism, especially with respect to process research methods.